2020
DOI: 10.1364/oe.389653
|View full text |Cite
|
Sign up to set email alerts
|

Enabling high repetition rate nonlinear THz science with a kilowatt-class sub-100 fs laser source

Abstract: Manipulating the atomic and electronic structure of matter with strong terahertz (THz) fields while probing the response with ultrafast pulses at x-ray free electron lasers (FELs) has offered unique insights into a multitude of physical phenomena in solid state and atomic physics. Recent upgrades of x-ray FEL facilities are pushing to much higher repetition rates, enabling unprecedented signal-to-noise ratio for pump probe experiments. This requires the development of suitable THz pump sources that are able to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…The time and space parts are coupled through the evolution of peak intensity and beam size. The model presented here is particularly well suited to describe propagation in nonlinear regenerative amplifiers [6], or MultiPass Cells (MPCs) [7][8][9][10], where it was shown that an injected Gaussian beam essentially retains its character upon propagation and that space-time couplings are only observed at extreme levels of nonlinearity [11,12]. Compared to the model presented in [11], that is purely (t,z) without a description of spatial effects, the model presented here allows to take into account Kerr lensing that can have non negligible impact on the beam caustic, as will be discussed hereunder.…”
Section: Introductionmentioning
confidence: 99%
“…The time and space parts are coupled through the evolution of peak intensity and beam size. The model presented here is particularly well suited to describe propagation in nonlinear regenerative amplifiers [6], or MultiPass Cells (MPCs) [7][8][9][10], where it was shown that an injected Gaussian beam essentially retains its character upon propagation and that space-time couplings are only observed at extreme levels of nonlinearity [11,12]. Compared to the model presented in [11], that is purely (t,z) without a description of spatial effects, the model presented here allows to take into account Kerr lensing that can have non negligible impact on the beam caustic, as will be discussed hereunder.…”
Section: Introductionmentioning
confidence: 99%
“…For the generation of those parameters, especially three laser architectures based on ytterbium-doped active media come into question. While thin-disk and slab lasers especially shine in terms of high pulse energies [4,5], ultrafast fiber lasers prevail in terms of average power [6] and pulse duration, owing to their broad gain bandwidth. However, largely exploiting it requires well thought out spectral shaping to counteract gain narrowing.…”
mentioning
confidence: 99%
“…In contrast, ultrafast Yb-based amplifiers are power-scalable into the kW regime [7][8][9], however, their output pulse duration is typically not shorter than 200 fs. Furthermore, highly efficient pulse compression in noble gasfilled compact multi-pass cells (MPC) has recently been utilized to compress the pulse duration of laser pulses in a broad energy range [2,[10][11][12][13][14][15][16]. Similar to gas-filled hollow-core-fiber (HCF) post-compression setups [17,18] the footprint of MPC setups scales with pulse energy leading to meter-scale assemblies in the multi-mJ range [2,11,12,15,16].…”
mentioning
confidence: 99%
“…At all points during the spectral broadening the residual propagation path in the chamber L prop is much smaller than the dispersion length L d [25] √ e = 8.1 under the assumption of a Gaussian pulse shape [26]. The chirp after the MPC is removed with a chirped-mirror compressor comprising six bounces off chirped mirrors each having a group delay dispersion (GDD) of -350 fs 2 . The total GDD is -1923 fs 2 after fine-tuning the compression with inserted glass plates.…”
mentioning
confidence: 99%
See 1 more Smart Citation